Patients with congenital heart disease over the age of 60: experiences of a single tertiary centre. (3rd October 2022) - Kecskemeti, D; Szabo, B; Nagy, Z S; Temesvari, A; Nagy, Z S; Szegedi, M; Nyolczas, N; Andreka, P; Balint, H
Abstract: Background: We are currently facing a shift in adult patients with congenital heart disease (ACHD) to older and more complex patients. The growing population of senior patients with congenital heart disease (CHD) is prone to acquired comorbidities. Purpose: Purpose of our study was to identify the main comorbidities in ACHD patients ≥60 years. Methods: 2726 patients had at least one visit at our ACHD centre between 2010 and 2021, 287 patients of them being 60 or older. Clinical data about the patients' last visit were obtained retrospectively from digital medical records. Based on the complexity of the CHD patients were classified as mild, moderate, and severe. Survival difference was analysed using the Kaplan-Meier method and the log rank test. Results: Senior patients included in this study were predominantly female (73.2%) with the median age of 69 years. We included 287 patients with mild (47.4%), moderate (39.4%), and severe (13.2%) underlying heart disease. Median age at first visit in our centre was 60 years (IQR 54–67). Over the median follow-up time of 7.9 years (IQR: 3.2–13.2), 20 patients (7%) died with the incidence of 0.8 deaths/100 patient years. The most common complication in this populations were Heart failure (43.2%) and arrhythmia (12.5%). Meanwhile the highest prevalence of heart failure was seen in patients with Eisenmenger syndrome/Pulmonary Arterial Hypertension (84.8%), Tetralogy of Fallot patients had the highest prevalence of arrhythmias (77.8%). 51% of all patients had at least one cardiovascular risk factor (diabetes, hypertension, hyperlipidaemia, or chronic kidney disease). 42% of the patients underwent a non-coronary intervention over the age of 60. The highest mortality was seen in patients with severely complex lesions (p<0.002). As of the comorbidities, significantly higher mortality was observed in seniors with heart failure (p=0.001) or NYHA functional class III/IV (p<0.002). Conclusions: Although the number of ACHD patients is growing constantly, the population of elderly patients with CHD is still mainly consists of patients with mild or moderate heart defects. Half of the patients had at least one cardiovascular risk factor by the age of 60. As expected, a significantly higher mortality was seen in those with severe heart defects. Funding Acknowledgement: Type of funding sources: None.